(untitled) (CIPEEX, 2025)
Introduction: Obesity is considered a pandemic disease as it has a high prevalence in both developed and developing countries and is associated with respiratory dysfunctions. The waist-to-hip ratio (WHR), in addition to being an indicator of obesity, is also considered a cardiovascular risk factor. Objective: To relate cardiovascular risk with pulmonary function in industrial sector workers. Methods: Analytical cross-sectional study involving workers from a construction materials industry. The sample consisted of 143 workers. The WC was calculated by dividing the waist circumference by the hip circumference, and respiratory function was measured by spirometry. The workers were stratified according to the WC (low and high risk). Results: 41 (28.7%) of the industry workers were at high risk, of which 25 were female. The age was higher in workers with high cardiovascular risk. The peak expiratory flow (PEF) ((∆=0.55 L/s, p<0.001), forced vital capacity (FVC) ((∆=0.65 L, p<0.001), %predicted FVC ((∆=14%, p<0.001), forced expiratory volume in the first second (FEV1) ((∆=0.55 L, p<0.001), %predicted FEV1 ((∆=11.18%, p<0.001) were higher in low-risk workers. There was a direct correlation of RCQ with PEF (r=0.26, p<0.001), FVC (r=0.22, p=0.009), and FEV1 (r=-0.19, p=0.021), while it was inverse for %FEV1predicted (r=0.35, p<0.001) and the FEV1/FVC ratio (r=-0.19, p=0.024). Conclusion: The pulmonary function of workers with low cardiovascular risk was better. However, a direct relationship was noted between WC and PEF, FVC, and MEF, and an inverse relationship when it comes to %FEVpredicted and FEV1/FVC ratio. For the prevention and promotion of cardiorespiratory health, it is suggested to encourage weight control, improve dietary quality, and increase the level of physical activity.